Translation of cultural aspects from English into Arabic: a case study of a dance of the forests - Harmoush, Doha Hisham; Moindjie, Mohamed Abdou; Shaidatul Akma Adi Kasuma, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Culture is about the mode of life and activity, way of thinking, and artifacts, which are associated with particular communities and the language which serves as a vehicle for meanings. This paper is aimed at describing cultural challenges and their translation procedures from English into Arabic; it also investigates choices of translation procedures that can be used to overcome cultural aspects problems. This study limits itself to cultural factors. It follows Newmark’s approach (1988) on culture translation. The corpus of this study is a play entitled A Dance of The Forests written by Wole Soyinka. The study is a qualitative study and cultural occurrences are analyzed and their translations are rated by raters who are native speakers of Arabic. The research reveals that translating a literary work like a play requires the use of strategies and procedures like domestication and oblique translation procedures, which are found to be vital in translating drama text from English into Arabic.